PERAN STAKEHOLDER DALAM PENGELOLAAN TAMAN WISATA ALAM GUNUNG TUNAK KABUPATEN LOMBOK TENGAH - Rahman, Muhamad Ari; Anwar, Hairil; Wahyuningsih, Endah (JURNAL RIMBA LESTARI, 2023)
The management of the Gunung Tunak Nature Tourism Park (TWA) requires collaboration among various stakeholders to achieve sustainable conservation and development. This study aims to identify stakeholders, analyze their influence and interests, and examine partnership patterns in the management of TWA Gunung Tunak. A descriptive method was employed in this research, using purposive sampling to select respondents. Data analysis utilized stakeholder analysis to evaluate the roles and relationships among actors. The results indicate the involvement of six key stakeholders in managing TWA Gunung Tunak: the West Nusa Tenggara Natural Resources Conservation Agency (BKSDA NTB), the Tourism Office of Central Lombok Regency, the Regional Development Planning Agency (Bappeda) of Central Lombok, the Korea-Indonesia Forest Cooperation Center (KIFC), the Mertak Village Government, and the Tunak Besopoq Group. Analysis revealed that BKSDA NTB and KIFC have very high levels of influence and interest in the management process, while the Tunak Besopoq Group exhibits high levels. In contrast, the Tourism Office, Bappeda Central Lombok, and Mertak Village Government display lower levels of influence and interest. The identified partnership patterns adhere to three main principles: equality and balance, transparency, and mutual benefit. These principles support effective collaborative management, emphasizing synergy among stakeholders to achieve conservation objectives and community empowerment.